Wishes, Lies, Dreams - Chutiwongpeti, Sarawut (InTensions, 2009)
I wish..., I hope..., I’m angry..., I’m afraid..., I’m sad..., I’m happy..., Come with me..... Wishes, Lies, Dreams (an ongoing three-dimensional mixed media installation) focuses on the mechanisms of perception and dreams, the private world between fantasy and unconsciousness, nature and the extra-ordinary, memory and immediacy: the conditions underlying the system by which mind and spirit operate. The (in)-visibility of this structure aims to ignite confusion as the viewer perceives the work and the space where it is placed. There is an intimacy here, but the story is unclear, cannot be clarified. Unlocking a mysterious force at the border of the truth and lie, Wishes, Lies, Dreams creates unexpected angles of approach, which in turn forces the viewer to take up a new position in the observation of the surrounding world. What can we learn, see, know, remember, feel between patterns of tranquillity and the disquieting? Entering the landscape of another’s dreams, provoked is an ambiguous relationship between the viewer, the object, its function and its appearance. Sarawut Chutiwongpeti graduated from the Department of Fine and Applied Arts at Chulalongkorn University in 1996. Winner of several awards, he has applied his artistic and research practice at the Banff Centre for the Arts (Canada), ImaginAsia Project, Smithsonian Institution (The Freer Gallery of Art and The Arthur M. Sackler Gallery, United State of America), ZKM Project, (Institute for Visual Media, Germany), Designskolen (Denmark), Fukuoka Asian Art Museum; Waseda University; Kobe University of Design (Japan), Central European University (Hungary), International Cultural Centre Jeunesses Musicales Croatia Groznjan (Croatia), The Nordland Kunst 0g Filmskole; The Trondheim Electronic Arts Centre; The Kunstakademiet Trondheim (Norway), Luleå Winter Biennial; The Beeoff/Splintermind; The Ricklundgården and The Royal University College of Fine Arts (Sweden); MAAP-Multimedia Art Asia Pacific, Nanyang Technological University (Singapore), Designing Your Future, Berlinale Talent Campus 2005, Haus der Kulturen der Welt (Germany) and Biennale Bibliotheca Alexandrina 2005, Arts Center, Bibliotheca Alexandrina (Egypt). For more information visit: http://www.chutiwongpeti.info